Public Sector Crisis Management - Rozanov, Alexander; Barannikov, Alexander; Belyaeva, Olga; Smirnov, Mikhail (IntechOpen, 2020)
The term "crisis management" was applied to business only after the publication of the monograph "Crisis Management: Planning for the Inevitable" by Steven Fink in 1986. Since then, this term has turned from a journalistic cliche into a scientific concept, and its concept, theory, and methodology have been further developed.It is the turning point in the meaning of the word "crisis" that indicates the possibility of changing the situation by making decisions that contribute to changing the vector of development of events from destruction to recovery and further development. From the above, the general definition of the term "crisis management" follows as a process of saving the system from its destructive effects. The activity of the crisis manager is always temporary and stops as a result of a favorable overcoming of the crisis or vice versa-the destruction of the system. Therefore, the criterion for the success of a manager in emergency crisis management is effectiveness as an absolute measure of the presence or absence of a result-it either exists or does not exist.